MENGUAK INFORMASI VIA ALEXA.COM SEBAGAI EVALUASI MENUJU OPTIMALISASI KEBERAKSESAN TERHADAP PERPUSTAKAAN DAN INSTITUSINYA - Wiji Suwarno (Central Library of Universitas Sebelas Maret, 2015)
Website institutions is an important part in order to promoting an institution to public widely. Website able to penetrate the various layers of society in a variety of conditions. Therefore, alexa.com initiative to calculate and make coarse count data of various possibilities for the treatment of society against the institution’s website, so that it can be made a ranking, a good popularity world-class website and the state level, people’s interest in the website, and also parts which websites most interested in a particular website’s home institution.